Reinforcement of religious moderation through role of chaplain in community police partnership forum from management perspective - Wibowo, Ardianto Bayu; Hartono, Bambang Dwi; Suprapto, Suprapto (ATTARBIYAH: Journal of Islamic Culture and Education, 2021)
The purpose of this study is to explain the importance of implementing enhancement of religious moderation in Indonesia and to find out the role of theologian in community police partnership forum as a mediator in resolving cases on religious issues, fostering people based on Islamic values, Pancasila and the Constitution of 1945 in amplify the establishment of the Republic of Indonesia. Furthermore, to identify the constraints faced and its solution from management perspective. The case study was chosen as the research method because it was considered to be able to capture the phenomenon of partnership between the police and the community to amplify the application of religious moderation. Reinforcement of religious moderation is considered important because it can support community harmony and order in living daily life in multicultural situations.The theologian of community police partnership forum can be a mediator in preventing the development of religious issues in Indonesia. The obstacle faced by the theologian is the lack of budget and structural and human resources. According to the SWOT analysis, what must be considered is the escort of theologians when they are mediators in conflict areas